A renal cell carcinoma with EWSR1‐TFE3 fusion gene. Issue 5 (4th December 2019) - Lang, Xing‐Ping; Pan, Jian; Yang, Chun‐Xiao; Chen, Ping; Shi, Chang‐Chun; Hong, Yang; Wang, Jian; Xiao, Sheng
Abstract: Both EWSR1 and TFE3 are well‐known oncogenes. EWSR1 encodes an RNA‐binding protein involved in multiple soft tissue tumors, including Ewing's sarcoma/peripheral neuroectodermal tumor, desmoplastic small round cell tumor, soft tissue clear cell sarcoma (malignant melanoma of soft parts), extraskeletal myxoid chondrosarcoma, and myxoid liposarcomas. TFE3 regulates both Golgi and lysosomal homeostasis and is rearranged in renal cell carcinoma (RCC), alveolar soft part sarcoma, epithelioid hemangioendothelioma, and perivascular epitheloid cell tumors (PEComas). In this report, we found a rare case of RCC with a fusion between 5′ EWSR1 and 3′ TFE3 . The fusion product retained most functional motifs of TFE3. The oncogenic mechanism likely involves TFE3 overexpression through its juxtaposition with the regulatory elements of EWSR1 and its translocation to the nucleus, resulting in the deregulation of Golgi and lysosomal homeostasis. This is a second case of RCC containing EWSR1‐TFE3 fusion.